Best Practices for Learning Based on Ecological Traditions and Local Culture of the Lambitu Community in Bima Regency - Fauzi, Azra; Otta, Gracia M. N.; Sriartha, I Putu; Mudana, Wayan; Pageh, I Made (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to formulate learning Best Practices based on the ecological traditions and local culture of the Lambitu community by integrating the values of Tri Hita Karana (THK). Employing a qualitative descriptive approach, data were collected through participatory observation, in-depth interviews with cultural leaders, local artisans, and educators, as well as documentation of cultural artifacts and ecological practices. The findings reveal a strong alignment between Lambitu’s cultural traditions and the three dimensions of THK—Parahyangan, Pawongan, and Palemahan—providing a pedagogical foundation for contextual and character-based learning. Five Best Practices were identified: Uma Lengge–based Eco–Ethno Learning, the “Adopt a Sacred Spring” conservation program, the Tembe Nggoli Character Project, the Eco–Craft Pandan Project, and the Mbolo Weki Education Forum. The study concludes that learning rooted in local culture supports holistic education that reflects harmonious relationships between humans, nature, and spirituality as conceptualized in THK values.